Genome-wide CRISPR/Cas9 Screen Identifies Host Factors Essential for Influenza Virus Replication - Julianna Han; Jasmine T. Perez; Cindy Chen; Yan Li; Asiel Benitez; Matheswaran Kandasamy; Yoontae Lee; Jorge Andrade; Benjamin tenOever; Balaji Manicassamy (Cell Reports, 2018)
Summary: The emergence of influenza A viruses (IAVs) from zoonotic reservoirs poses a great threat to human health. As seasonal vaccines are ineffective against zoonotic strains, and newly transmitted viruses can quickly acquire drug resistance, there remains a need for host-directed therapeutics against IAVs. Here, we performed a genome-scale CRISPR/Cas9 knockout screen in human lung epithelial cells with a human isolate of an avian H5N1 strain. Several genes involved in sialic acid biosynthesis and related glycosylation pathways were highly enriched post-H5N1 selection, including SLC35A1, a sialic acid transporter essential for IAV receptor expression and thus viral entry. Importantly, we have identified capicua (CIC) as a negative regulator of cell-intrinsic immunity, as loss of CIC resulted in heightened antiviral responses and restricted replication of multiple viruses. Therefore, our study demonstrates that the CRISPR/Cas9 system can be utilized for the discovery of host factors critical for the replication of intracellular pathogens. : Using a genome-wide CRISPR/Cas9 screen, Han et al. demonstrate that the major hit, the sialic acid transporter SLC35A1, is an essential host factor for IAV entry. In addition, they identify the DNA-binding transcriptional repressor CIC as a negative regulator of cell-intrinsic immunity. Keywords: CRISPR/Cas9 screen, GeCKO, influenza virus, host factors, sialic acid pathway, SLC35A1, Capicua, CIC, cell-intrinsic immunity, H5N1